Fabrication and modeling of recessed traces for silicon-based neural microelectrodes. (7th October 2020) - Nolta, Nicholas F; Ghelich, Pejman; Ersöz, Alpaslan; Han, Martin
Abstract: Objective. Chronically-implanted neural microelectrodes are powerful tools for neuroscience research and emerging clinical applications, but their usefulness is limited by their tendency to fail after months in vivo . One failure mode is the degradation of insulation materials that protect the conductive traces from the saline environment. Approach. Studies have shown that material degradation is accelerated by mechanical stresses, which tend to concentrate on raised topographies such as conducting traces. Therefore, to avoid raised topographies, we developed a fabrication technique that recesses (buries) the traces in dry-etched, self-aligned trenches. Main results. The fabrication technique produced flatness within approximately 15 nm. Finite element modeling showed that the recessed geometry would be expected to reduce intrinsic stress concentrations in the insulation layers. Finally, in vitro electrochemical tests confirmed that recessed traces had robust recording and stimulation capabilities that were comparable to an established non-recessed device design. Significance. Our recessed trace fabrication technique requires no extra masks, is easy to integrate with existing processes, and is likely to improve the long-term performance of implantable neural devices.